Gain enhancement of perovskite nanosheets by a patterned waveguide: excitation and temperature dependence of gain saturation - Kim, I; Choi, GE; Mei, M; Kim, MW; Kim, M; Kwon, YW; Jeong, T-I; Kim, S; Hong, SW; Kyhm, K; Taylor, RA (Springer Nature, 2023)
Optical gain enhancement of two-dimensional CsPbBr3 nanosheets was studied when the amplified spontaneous emission is guided by a patterned structure of polyurethane-acrylate. Given the uncertainties and pitfalls in retrieving a gain coefficient from the variable stripe length method, a gain contour g(ℏω, x) was obtained in the plane of spectrum energy (ℏω) and stripe length (x), whereby an average gain was obtained, and gain saturation was analysed. Excitation and temperature dependence of the gain contour show that the waveguide enhances both gain and thermal stability due to the increased optical confinement and heat dissipation, and the gain origins were attributed to the two-dimensional excitons and the localized states.